Letter From the Editor - Regina Hoffman (Patient Safety, 2019)
Thank you to every reader, author, reviewer, editorial board member, and staff person for making the launch of Patient Safety a success. In a short period of time, nearly 7,000 people from over 120 countries and all 50 United States read the inaugural issue. I also extend a special thanks to our patient representatives, who dedicate their time and energy through this journal and many other initiatives to make care safer for others.Our December issue features a patient perspective piece by Kristin Aaron, who shares the tragic healthcare journey of her son, Jenson (featured on our cover), and how great change often starts with a single step. Our back inside cover features The Walking Gallery jacket #160 Cancer for Christmas. Casey Quinlan, diagnosed with breast cancer just days before Christmas in 2007, leveraged her experience to help others navigate cancer treatment. Quinlan was a charter author for Patients Included™, a nonprofit inspiring organizations to include patients in their work. I am proud to say Patient Safety is a Patients Included™ publication.Also from our cover: Cait Allen, director of engagement and managing editor with the Patient Safety Authority, sat down with Kathleen Noonan, chief executive officer of the Camden Coalition of Healthcare Providers, to talk about some innovative solutions to meet the needs of a very at-risk population. Elizabeth Kukielka and co-authors discuss the findings of a database analysis related to telemetry monitoring; this article was inspired by a deep dive into events in Pennsylvania that cause high harm and death to patients. And finally, Sara Kolc Brown and co-authors share one facility’s initiative to decrease adverse drug events by using trigger tools. Their work contributes to further development of prevention strategies.I never imagined that one of the most difficult tasks in the publication process would be selecting the papers to feature on our cover. There are so many that equally deserve the spotlight. I hope this will continue to challenge me with each issue. The information, achievements, risk reduction strategies, lessons learned, and individual perspectives are integral pieces to improving patient safety for all. This journal is one avenue to share these valuable resources freely with others. If you have research, improvement initiatives, or perspectives that contribute to our collective knowledge, please consider submitting your next manuscript to Patient Safety at patientsafetyj.com.Wishing you and yours the most joyous holiday season!